2020
DOI: 10.1109/jeds.2020.2966680
|View full text |Cite
|
Sign up to set email alerts
|

A Silicon Carbide 256 Pixel UV Image Sensor Array Operating at 400 °C

Abstract: An image sensor based on wide band gap silicon carbide (SiC) has the merits of high temperature operation and ultraviolet (UV) detection. To realize a SiC-based image sensor the challenge of opto-electronic on-chip integration of SiC photodetectors and digital electronic circuits must be addressed. Here, we demonstrate a novel SiC image sensor based on our in-house bipolar technology. The sensing part has 256 (16×16) pixels. The digital circuit part for row and column selection contains two 4-to-16 decoders an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…This brings the total readout time down to 2.6 s, or 0.39 Hz, which is a 13 times improvement to the synchronous clock. As a fair comparison to the reported 256 pixel array in a SiC BJT technology 15 the timing scheme is extrapolated, resulting in a total time for 256 pixels of 8.4 s, which is an improvement of 15 times.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This brings the total readout time down to 2.6 s, or 0.39 Hz, which is a 13 times improvement to the synchronous clock. As a fair comparison to the reported 256 pixel array in a SiC BJT technology 15 the timing scheme is extrapolated, resulting in a total time for 256 pixels of 8.4 s, which is an improvement of 15 times.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive research effort was made on silicon carbide photodetectors, as they make excellent visual-blind UV detectors. Over the years the technology has come a long way, leading for example to a UV-index monitoring demonstrator board 14 and UV imager 15 . Reliability studies on the aging effects show promising results, revealing little to no change in the device performance 16 – 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shakir et al demonstrated a SiC 555 timer and a SiC comparator that are operational under 500°C [14] with an in-house SiC bipolar junction transistor (BJT) process [15]. Hou et al reported a 16x16 SiC UV image sensor array operating at 400°C with the same BJT technology [16]. Research groups from NASA and Ohio Aerospace Institute [17] have also demonstrated SiC JFET digital ICs that operate across a wide range of temperatures (−190°C to 812°C).…”
Section: Introductionmentioning
confidence: 99%
“…Operation of 4H-SiC bipolar junction transistors (BJTs), junction field effect transistors (JFETs), and metal-oxide-semiconductor transistors (MOSFETs) have been demonstrated in high temperature environments [4][5][6][7][8][9][10][11][12][13][14]. In terms of the image sensor, 4H-SiC has already demonstrated operation as a UV imaging system with 256 pixels at 400°C [15]. However, 4H-SiC does not have sufficient absorbance at visible light [16].…”
Section: Introductionmentioning
confidence: 99%